2013
DOI: 10.1016/j.cub.2013.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Assembly Checkpoint of Oocytes Depends on a Kinetochore Structure Determined by Cohesin in Meiosis I

Abstract: SummarySince the dissolution of sister chromatid cohesion by separase and cyclin B destruction is irreversible, it is essential to delay both until all chromosomes have bioriented on the mitotic spindle. Kinetochores that are not correctly attached to the spindle generate the mitotic checkpoint complex (MCC), which inhibits the anaphase-promoting complex/cyclosome (APC/C) and blocks anaphase onset. This process is known as the spindle assembly checkpoint (SAC) [1]. The SAC is especially important in meiosis I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…Consistent with this, sister kinetochores of univalent chromosomes frequently establish microtubule attachments with both poles of the MI spindle in mouse oocytes (Le Maire-Adkins et al 1997;Kouznetsova et al 2007;Nagaoka et al 2011) and yeast (Sakuno et al 2011). Indeed, recent findings indicate that cleavage of Rec8 specifically at centromeres promotes biorientation of univalent chromosomes in mouse oocytes (Tachibana-Konwalski et al 2013). This suggests that, as in fission yeast, centromeric Rec8 is important for mono-orientation of sister kinetochores in mammalian oocytes.…”
Section: Molecular Mechanisms Of Meiosis and Aneuploidy: Chromosome Smentioning
confidence: 60%
“…Consistent with this, sister kinetochores of univalent chromosomes frequently establish microtubule attachments with both poles of the MI spindle in mouse oocytes (Le Maire-Adkins et al 1997;Kouznetsova et al 2007;Nagaoka et al 2011) and yeast (Sakuno et al 2011). Indeed, recent findings indicate that cleavage of Rec8 specifically at centromeres promotes biorientation of univalent chromosomes in mouse oocytes (Tachibana-Konwalski et al 2013). This suggests that, as in fission yeast, centromeric Rec8 is important for mono-orientation of sister kinetochores in mammalian oocytes.…”
Section: Molecular Mechanisms Of Meiosis and Aneuploidy: Chromosome Smentioning
confidence: 60%
“…It is interesting to note there might be some association between reduced SAC proteins and cohesion loss with maternal age, which is supported by a recent report showing that cohesin deterioration may compromise SAC function by impairing sister kinetochore biorientation and its SAC signal production in mouse oocytes. 67 Despite a 25-50% fall in Mad2 and pAurora C on kinetochores that might indicate a reduced SAC activity in aged oocytes, it is highly unlikely that the SAC is completely non-functional. This is because MI duration was not shortened with age, a finding consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…BUBR1 has an additional role in stabilizing kinetochore-microtubule attachments, and BUB1 is required to prevent precocious sister chromatid segregation in meiosis I undergo metaphase-to-anaphase transition of meiosis I. Results from MLH1 −/− mice indicate that robust activation of the spindle checkpoint in oocytes depends additionally on the strain background used: In the different strains, most chromosomes in MLH1 −/− oocytes are univalents because MLH1 is required for recombination and chiasmata formation, but whether anaphase I onset is only delayed or inhibited due to checkpoint activation depends on the strain background (Nagaoka et al 2011;Tachibana-Konwalski et al 2013;Woods et al 1999). …”
Section: Mouse Oocytes Have a Spindle Checkpoint Too!mentioning
confidence: 99%
“…Single sister chromatids are not recognized as wrong in meiosis I and do not lead to a metaphase I arrest, as long as they are not maintained together with their sister through centromeric cohesin (Tachibana-Konwalski et al 2013). A recent study has identified a novel, meiosisspecific mammalian protein, named MEIKIN, that is partly required for mono-orientation of sister kinetochores and cohesin protection in meiosis I (Kim et al 2015).…”
Section: Mono-orientation and The Spindle Checkpointmentioning
confidence: 99%